Contributions of Working Conditions on Teachers’ Attitude in School Settings of Nepal - Anan Lama; Milan Shrestha (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose- Working conditions play an important role in shaping the teachers’ attitude. In this context, this study intends to examine the effect of the working conditions on the teachers’ attitude. Design/Methodology- Philosophically, this study is guided by post-positivist paradigm utilizing the survey design. The data in this study were collected from the teachers of community schools of the Kathmandu district using the questionnaire My Classroom Appraisal Protocol (MCAP). The collected data were analyzed using both descriptive and inferential statistics like mean, standard deviation, independent sample t-test and simple linear regression. Then, the derived findings were then interpreted and measured against the past studies and theories. Findings- This study found significant difference in the attitude of the teachers who had satisfactory and unsatisfactory building conditions. Additionally, the study showed a moderate association between working condition and teachers’ attitude. Furthermore, this study concludes that the building condition of school plays a crucial role in shaping the teachers’ attitude. Finally, this study shows that there is a positive relationship between the working conditions and teachers’ attitude. Practical Implications- This study is expected to be beneficial to school leaders and forthcoming researchers for making positive changes in the education system of Nepal.